MENGEMBANGKAN KEWIRAUSAHAAN MELALUI PENDIDIKAN KARAKTER UNTUK MEMBANGUN SUMBER DAYA MANUSIA DIBIDANG INDUSTRI KREATIF DI POLITEKNIK NEGERI MEDIA KREATIF - Purnomo Ananto; Anindita Budi Astuti (Jurnal Ilmiah Publipreneur, 2018)
As vocational colleges that educate and develop human resources in the field of creative industries, Creative Media Polytechnic (PoliMedia) does not use models or technology-based entrepreneurship technopreneur but PoliMedia develop entrepreneurship-based creative industries to economic development kreatif.di Indonesia. Character education developed in PoliMedia intended to allow the students to have creative and innovative character, honest, willing to take risks, responsibilities, tough, independent, disciplined and ultimately capable of being characterized as workers or entrepreneurs. Â Entrepreneurship development through Character Education in Creative Media Polytechnic carried out through three channels, namely: the path of academic / curricular courses delivered through Entrepreneurship, Education Pancasila and Citizenship Education and Religious Education: the path extracurricular activities conducted through Entrepreneurship, Unit of Student Activities such as Sports and Arts . Meanwhile, other supporting activities is through the activities of public lectures delivered by resource persons, especially in the field of character education and success stories of entrepreneurs, as well as through integration by other lecturers lecturer; The third track is done through the management of the institutional Polimedia PoliMedia done through the planning both academic and non academic, entrepreneurial developers team up, forming a business unit as well as applying some rules aimed at improving student behavior and character, such as a ban on smoking on campus and to create a clean and green campus to provide exemplary and an atmosphere conducive to learning . Of the 14 who developed the Creative Industries sector in Indonesia, PoliMedia currently developing five sectors, namely: Printing and Publishing; Interactive Games: Graphic Design: Photography and Advertising is done through the 8 existing study programs and students are always encouraged to become entrepreneurs in Creative Industries sector that became peminatannya, which is known as the creative industry is an industry that lead to the intellect, ideas, and an original idea by thinking and feeling from my heart most deeply.